97 Complexity In Croydon. (6th February 2020) - Smith, J; Gass, N; Huntley, M; Nanuck, R; Vandendris, S; Bell, C; Heitz, E; Wilson, T
Abstract: Introduction: The Complex Care Support Team (CCST) are a newly-formed, integrated service, caring for Croydon residents when existing services decide additional multidisciplinary team input is required. There is no single definition of healthcare complexity. Most cases encountered by the team have involved many different services and professionals. The team have found that by forging relationships and co-ordinating care across organisational boundaries, some of the "complexities" can be mitigated. We aim to develop our understanding of the needs of this population and the underlying drivers for complexity in Croydon. Methods: The records on EMIS, CERNER and ePJS were reviewed from the inaugural two months of the service, for: Rockwood Frailty Score Number of medications Number of long-term conditions ED attendances or admissions to hospital over the preceding year. After team discussion on every case, underlying causes of complexity were assigned to four groups: medical, psychological, social and systems failure. Results: Of the 57 people accepted by CCST over 2 months, 39 required reviewing in person. 5 records were not completed, so 34 cases were included for evaluation. The age range of this cohort was 49-92, with 17 male and 17 female. Results revealed significant frailty, multimorbidity and polypharmacy. 91% had two or more underlying drivers for complexity, with the largest underlying driver being systems failure, in 85% of cases. Conclusions: This work improves our understanding of the needs of the population deemed the most "complex" in Croydon. The likelihood of multiple underlying drivers for complexity was high, highlighting how complex health issues are likely to span both professional and organisational boundaries. This can in itself be a significant underlying driver for complexity, illustrated here as "systems failure". In developing current and future services, this work reinforces the vital benefits of multidisciplinary and cross-organisational working currently occurring in CCST.